2019
DOI: 10.1111/tmi.13234
|View full text |Cite
|
Sign up to set email alerts
|

Programmatic outcomes and impact of rapid public sector antiretroviral therapy expansion in adults prior to introduction of the WHO treat‐all approach in rural Eswatini

Abstract: ObjectivesTo assess long‐term antiretroviral therapy (ART) outcomes during rapid HIV programme expansion in the public sector of Eswatini (formerly Swaziland).MethodsThis is a retrospectively established cohort of HIV‐positive adults (≥16 years) who started first‐line ART in 25 health facilities in Shiselweni (Eswatini) between 01/2006 and 12/2014. Temporal trends in ART attrition, treatment expansion and ART coverage were described over 9 years. We used flexible parametric survival models to assess the relati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 58 publications
2
15
0
Order By: Relevance
“…Firstly, the rapid decentralisation of HIV-TB services between 2008 and 2010 may have improved access to diagnosis and case detection of active TB for this predominantly rural population. Secondly, ART coverage increased rapidly in this high-HIV prevalence setting, from an estimated 7.1% in 2006 [42] to 82.7% in 2016/2017 [43]. In southern Africa, expansion of HIV treatment and high ART coverage are suggested key factors to decrease the burden of TB in people living with HIV and possibly also in the HIV-negative population [44].…”
Section: Findings In Contextmentioning
confidence: 99%
“…Firstly, the rapid decentralisation of HIV-TB services between 2008 and 2010 may have improved access to diagnosis and case detection of active TB for this predominantly rural population. Secondly, ART coverage increased rapidly in this high-HIV prevalence setting, from an estimated 7.1% in 2006 [42] to 82.7% in 2016/2017 [43]. In southern Africa, expansion of HIV treatment and high ART coverage are suggested key factors to decrease the burden of TB in people living with HIV and possibly also in the HIV-negative population [44].…”
Section: Findings In Contextmentioning
confidence: 99%
“…In several cohort studies of ART programmes in sub-Saharan Africa, there have been reports of higher rates of LTFU among patients who initiated ART in later years compared to earlier years (26)(27)(28). This may be explained by patients increasingly initiating treatment while less severely ill (29), as well as a negative consequence of patient numbers increasing such as facility workloads (30), raising concerns about the sustainability of these programmes. Some systematic reviews have shown that the percentage of patients LTFU who have died has decreased in later years as eligibility criteria have evolved to include less immunologically compromised patients, and as the proportion of patients LTFU has increased (13,31).…”
Section: Introductionmentioning
confidence: 99%
“…Overall retention was comparable to ART programmes in low‐ and middle‐income countries and two Treat‐All trials in Southern Africa . However, point estimates of retention tended to be lower than under SOC, than previous retention estimates from this setting before the introduction of Treat‐All and than in a streamlined combination intervention trial in Eastern Africa . Similarly to another Treat‐All trial in South Africa , 6% of patients never returned for a clinic visit after ART initiation (vs. 3% under SOC).…”
Section: Discussionmentioning
confidence: 61%
“…The setting has been described previously . The predominantly rural Shiselweni region has a population of ~210,000 and HIV prevalence is 31% in 18‐ to 49‐year‐olds .…”
Section: Methodsmentioning
confidence: 99%